Controle de Senecio spp. com pastoreio ovino de acordo com a infestação e fenologia da planta e a influência da cobertura vegetal - Karam, Fernando Sérgio Castilhos (2012)
The present study yielded a review article on the intoxication by Senecio spp. (seneciosis) and on the control measures for this important cause of death among cattle in the state of Rio Grande do Sul (RS), Brazil. Given that no efficient treatment exists, measures that combine the biological control of the plant and the proper management of agricultural land can reduce economic losses. The study also included two experiments one on the influence of vegetation cover on the germination and emergence of Senecio spp. from seeds in the soil, using three management practices in naturally infested areas: 1) plowing with planting; 2) plowing without planting and 3) slashing and mulching; observed fortnightly for one year. Germination was higher (73.1%) where the land was exposed, without planting. In the three areas, June was the month in which emergence was higher (75.6%). The results reveal the importance of vegetation cover for germination and maintenance of the plant in the environment, in addition to the special care needed at this stage and in this region, when the analyzed species are potentially more toxic. This experiment was presented in a seminar (poster session) and will be replicated in other areas for analysis in different environments and regions. Given that sheep are more resistant to the toxic alkaloids released by Senecio spp. and are natural controls against this plant, the aim of the other experiment (second article) was to assess the efficiency of sheep grazing in different seasons of the year in order to determine the best time for interference in the phenology of this plant and infestation of the pastures. The experiment was carried out in four plots, two sheep by plot (50m X 100m), with different levels of infestation, on two farms in southern RS. The level of infestation, regardless of the species, was determined by the average number of plants in each plot and determined by quantity of plants in each one of twelve points (2m diameter each) phenological observation: presence of 1 to 3 plants indicated low infestation (LI) and 4 to 6 plants indicated average infestation (AI), both observed on farm A; whereas 7 to 9 plants meant high infestation (HI) and 10 plants or more were regarded as very high infestation (VHI), both on farm B. In those points the following parameters were evaluated on day 0 (before the introduction of sheep) and at fortnightly intervals in the spring of 2009 (year 1) and in the winter and spring of 2010 (year 2): number of specimens of Senecio species, reproductive phenophases, vigor, and plant consumption by the sheep. The analysis of variance was used for the continuous quantitative variable (number of plants) while the Tukey test was used for comparison of the means. The chi-square test was used for comparison of the qualitative variables (reproductive phenophase, vigor, and consumption of the plants by the sheep). Significant factors included season of the year (spring and winter), infestation (VHI, HI, AI, LI), treatment (control and plots) and first-order interactions. A P<0.05 was set as significant for all analyses. In year 1, infestation was significant for the number of plants and the averages differed at the infestation levels. In year 2, season of the year, infestation and treatment were significant for the number of plants and their interactions, except for the interaction between season of the year and infestation. Infestation and treatment were significant for the reproductive phenophase and for vigor, and treatment was also significant for consumption of the plants by the sheep. The results demonstrate the influence of sheep grazing at different levels on the analyzed variables as far as various effects, always negative for plant growth, are concerned. Taking into account the phenological and environmental conditions, especially the season in which the cattle were at higher risk, sheep grazing controls Senecio spp. more efficiently during the winter time, providing biological control of the plant and reducing infestation and losses in cattle farming in RS.